A NEW COMPLEX CONSERVATIVE METHOD FOR TREATMENT OF SKIN LEISHMANIOSIS (ResearchJet Journal of Analysis and Inventions, 2021)
In our study, we set a goal to evaluate the effectiveness of a comprehensive treatment method for the treatment of cutaneous leishmanillosis. We treated 30 patients with cutaneous leishmaniasis. Of these, 15 had facial lesions, 7 had leishmaniasis ulcers on the upper extremities, and 8 had combined leishmaniasis, meaning ulcers were found on the face, body, and limbs. The age of patients ranges from 6 months to 65 years.